MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN DENGAN MENGGUNAKAN METODE ALTMAN Z – SCORE (Studi Kasus pada Perusahaan Retail yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Ghea B Astrid Sunanto; Sunanto Sunanto; Agus Suhartono (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to examine the effect of Working Capital to Total Assets, Retained Earning to Total Assets and Earning Before Interest and Taxs Ratio To Total Assets on financial distress. Sampling using the purposive sampling method obtained a sample of 5 companies with 25 data. The population in this study is retail trading companies in the retail sector on the Indonesia Stock Exchange for the 2016–2020 financial year. The regression method in this study is simple and multiple linear regression. Regression results show that there is a significant relationship between Working Capital to Total Assets and Earning Before Interest And Taxs Ratio To Total Assets to financial distress. This means that the company is experiencing financial condition difficulties, namely difficulty meeting current obligations and low revenues that affect the company's bankruptcy. The results of the regression test showed that there was no significant relationship between Retained Earnings to Total Assets and financial distress. This means that the company shows sufficient ability to generate retained earnings from the total assets owned by the company.